Lectotipificaciones en Hybanthus Jacq. (Violaceae) de la flora nativa de Argentina y Paraguay - Seo, Micaela Noemi (2009)
Hybanthus melchiorianus Schulze-Menz and Hybanthus velutinus Schulze-Menz (Violaceae) are lectotypified from E. Hassler’s collections in G, since their holotypes conserved in B were destroyed.